Homocystein Level in Patient with Ischemic Heart Disease and Some Associated Diseases - Merza Al-Araji, Saad; H. Abbase, Ala; F. Hassan, Zainab (Asian Journal of Chemistry, 2012)
Homocysteine is an intermediate of methionine metabolism which, at elevated levels, is an independent risk factor for vascular disease and atherosclerosis. This study includes the determination of homocysteine level in random serum of patients with pure ischemia, ischemia with hypertension and ischemia with diabetes who attended Merjan teaching hospital in Hilla city, Babylon province, Iraq, from August, 2008 to May, 2009. Patients were divided into three groups; 23 patients had pure ischemic heart disease (17 males and 6 females), 16 had ischemic heart disease with hypertension (10 males and 6 females), 18 had ischemia heart disease with diabetes (8 males and 10 females). The control group consisted of 40 normal individuals who did not have any symptoms for ischemic heart disease and were gender and age-matched with the patients. Homocysteine level was measured by high performance liquid chromatography after deproteinized blood sample with 15 % 5 -sulphosalicylic acid. Homocysteine level was significantly increased (P < 0.01) in pure ischemic patients, ischemia with hypertension and ischemia with diabetes in comparison with control group. A comparison had also been done between male and female groups in patients and control groups and no significant changes (P > 0.05) were observed.